Urban Catalyst Element Impact on the Pattern of Spatial Distribution in Semarang City Border Area - Setioko, Bambang; KW, Mustika; WM, Titien (International Journal of Engineering and Technology, 2018)
In recent decades the urban growth in Indonesia is likely to follow a global urban trend, characterized by peripheral urbanization. This phenomenon has potentially encouraged the growth of urban physical area to be very broad and unlimited, and often exceeds the city administrative boundary. The urban catalyst development in the eastern city accelerates the growth of settlement in the border area; while the visually of both amongst the border area and the urban area are similar. This research was conducted in Sendang Mulyo village located in the administrative area of Semarang City and in Pucang Gading village located in, Demak Region. This study aims to determine the effect of urban catalyst element on the pattern of spatial distribution in the border area of Semarang City and Demak Region. Based on literature study that has been done, this research uses a quantitative approach with descriptive method under of rationalistic paradigm. Statistical data analysis is done by regression test using software SPSS 16.0. The results of this study indicate the growth and development of urban catalyst elements in the eastern part of Semarang city, significantly has impact to the pattern of spatial distribution in the border area of the Semarang city significantly.Â Â